2022
DOI: 10.3897/folmed.64.e62272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of earthworm oil on formation of collagen type III during wound healing process in BALB/c mice

Abstract: Introduction: Eisenia fetida is a species of earthworm. The oil extracted from this species has been found to have antimicrobial and antioxidant characteristics as well as omega-3, omega-6, and omega-9 fatty acids in its contents. The regenerative properties of this compound are very impressive. Aim: This study aimed to evaluate the effect of earthworm oil on wound healing based on collagen type III formation in the BALB/c mice. Materials and methods: The present experimental study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“… 47 , 48 Increasing the amount and organization of collagen with many agents used has been directly associated with accelerating and improving the wound repair process. 49 , 50 , 51 , 52 , 53 , 54 , 55 In an in vivo model, in which the effect of calcium alginate on wounds was examined and parallel to our study, it was reported that COLI expression increased from the 3rd day to the 14th day in the treated group, and there was no significant difference in COLIII expressions between the two groups. 56 Ganeshkumar et al showed that topically applied Acalypha indica extract improved cellular proliferation by significantly increasing the expression of COLI (150%) and COLIII (180%) on the 7th day of scar tissue.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“… 47 , 48 Increasing the amount and organization of collagen with many agents used has been directly associated with accelerating and improving the wound repair process. 49 , 50 , 51 , 52 , 53 , 54 , 55 In an in vivo model, in which the effect of calcium alginate on wounds was examined and parallel to our study, it was reported that COLI expression increased from the 3rd day to the 14th day in the treated group, and there was no significant difference in COLIII expressions between the two groups. 56 Ganeshkumar et al showed that topically applied Acalypha indica extract improved cellular proliferation by significantly increasing the expression of COLI (150%) and COLIII (180%) on the 7th day of scar tissue.…”
Section: Discussionsupporting
confidence: 77%
“…Thus, the highest percentage of type I collagen compared to Type III collagen indicates the collagen maturation status 47,48 . Increasing the amount and organization of collagen with many agents used has been directly associated with accelerating and improving the wound repair process 49–55 . In an in vivo model, in which the effect of calcium alginate on wounds was examined and parallel to our study, it was reported that COLI expression increased from the 3rd day to the 14th day in the treated group, and there was no significant difference in COLIII expressions between the two groups 56 .…”
Section: Discussionsupporting
confidence: 69%
“…While these testimonials provide valuable insights into the real-world experiences of users, they complement the rigorous scientific research that forms the cornerstone of our understanding of earthworm-based skincare's effects. This convergence of empirical evidence from both controlled studies and user feedback serves to fortify the argument for earthworm-derived skincare as a promising avenue in the quest for effective anti-aging solutions (Afshar et al, 2022).…”
Section: Introductionmentioning
confidence: 93%
“…Clinical trials, laboratory analyses, and user testimonials collectively bolster the argument for their inclusion in skincare formulations. Rigorous testing and peer-reviewed studies have begun to substantiate the claims of improved skin texture, reduced fine lines, and enhanced hydration with consistent application of earthwormbased skincare products (Afshar et al, 2022).…”
Section: Salem Et Al (2022)mentioning
confidence: 99%
“…Disruptions in this process can lead to delayed or impaired healing. 15 , 16 In the following section, each stage will be explained in detail.…”
Section: Wound Healingmentioning
confidence: 99%